1991
DOI: 10.1021/bi00242a020
|View full text |Cite
|
Sign up to set email alerts
|

Neutral imidazole is the electrophile in the reaction catalyzed by triosephosphate isomerase: structural origins and catalytic implications

Abstract: To illuminate the role of histidine-95 in the catalytic reaction mediated by triosephosphate isomerase, 13C and 15N NMR titration studies have been carried out both on the wild-type enzyme and on a mutant isomerase in which the single remaining histidine (that at the active site) has been isotopically enriched in the imidazole ring. 15N NMR has proved especially useful in the unambiguous demonstration that the imidazole ring of histidine-95 is uncharged over the entire pH range of isomerase activity, between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
184
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(192 citation statements)
references
References 44 publications
(40 reference statements)
8
184
0
Order By: Relevance
“…As for all other TIM structures, the hydrogen bonding context of His-95 suggests that it is neutral, and protonated at the (amino) N position. Previous NMR studies demonstrated that the imidazole group is neutral at physiological pH values (13). In the Michaelis complex structure, the imino N␦ forms a hydrogen bond with an amidic NH moiety from the protein backbone; N forms a bifurcated hydrogen bond to O2 (2.6-2.7 Å) and O1 (3.0 Å) of the substrate (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…As for all other TIM structures, the hydrogen bonding context of His-95 suggests that it is neutral, and protonated at the (amino) N position. Previous NMR studies demonstrated that the imidazole group is neutral at physiological pH values (13). In the Michaelis complex structure, the imino N␦ forms a hydrogen bond with an amidic NH moiety from the protein backbone; N forms a bifurcated hydrogen bond to O2 (2.6-2.7 Å) and O1 (3.0 Å) of the substrate (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…This electrophile has a crucial kinetic role in facilitating proton transfer, as evidenced by the disastrous effects on k cat when it is replaced by other functionalities (16). Short hydrogen bonds involving His-95 and analog compounds have been characterized with diffraction (9), IR (16), and NMR experiments (13,17), as well as with computational tools (19). The structures reported herein, at nearatomic resolution, allowed us to define the hydrogen bonding parameters in the presence of the actual substrate for the first time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extraordinary efficiency of TIM (23) and KSI (24) (k cat /K m Ϸ10 8 M Ϫ1 s Ϫ1 ), for instance, arises from synergistic action of a carboxylate base, which initiates proton abstraction from carbon, and a general acid, either a histidine (25) or a tyrosine (26), that stabilizes the resulting anionic intermediate via hydrogen bonding.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include changes in 31P chemical shifts to study phosphate pKas (Vogel, 1989), "&l, and ISNf2 chemical shifts of histidine imidazole groups (Bachovchin, 1986;van Dijk et al, 1990van Dijk et al, . 1992Lodi & Knowles, 1991;Annand et al, 1993;Pelton et al, 1993;Tsilikonas et al, 1996) and I3C side chain carboxyl chemical shifts for aspartic and glutamic acid residues (Jeng & Dyson, 1996;Qin et al, 1996).…”
mentioning
confidence: 99%